Dissonant health transition in the states of Mexico, 1990–2013: a systematic analysis for the Global Burden of Disease Study 2013. Issue 10058 (12th November 2016) - Gómez-Dantés, Héctor; Fullman, Nancy; Lamadrid-Figueroa, Héctor; Cahuana-Hurtado, Lucero; Darney, Blair; Avila-Burgos, Leticia; Correa-Rotter, Ricardo; Rivera, Juan A; Barquera, Simon; González-Pier, Eduardo; Aburto-Soto, Tania; de Castro, Elga Filipa Amorin; et al.
Summary: Background: Child and maternal health outcomes have notably improved in Mexico since 1990, whereas rising adult mortality rates defy traditional epidemiological transition models in which decreased death rates occur across all ages. These trends suggest Mexico is experiencing a more complex, dissonant health transition than historically observed. Enduring inequalities between states further emphasise the need for more detailed health assessments over time. The Global Burden of Diseases, Injuries, and Risk Factors Study 2013 (GBD 2013) provides the comprehensive, comparable framework through which such national and subnational analyses can occur. This study offers a state-level quantification of disease burden and risk factor attribution in Mexico for the first time. Methods: We extracted data from GBD 2013 to assess mortality, causes of death, years of life lost (YLLs), years lived with disability (YLDs), disability-adjusted life-years (DALYs), and healthy life expectancy (HALE) in Mexico and its 32 states, along with eight comparator countries in the Americas. States were grouped by Marginalisation Index scores to compare subnational burden along a socioeconomic dimension. We split extracted data by state and applied GBD methods to generate estimates of burden, and attributable burden due to behavioural, metabolic, and environmental or occupational risks. We present results for 306 causes, 2337 sequelae, and 79 risk factors. Findings: From 1990 to 2013, life expectancy from birth in Mexico increased by 3·4 years (95% uncertainty interval 3·1–3·8), from 72·1 years (71·8–72·3) to 75·5 years (75·3–75·7), and these gains were more pronounced in states with high marginalisation. Nationally, age-standardised death rates fell 13·3% (11·9–14·6%) since 1990, but state-level reductions for all-cause mortality varied and gaps between life expectancy and years lived in full health, as measured by HALE, widened in several states. Progress in women's life expectancy exceeded that of men, in whom negligible improvements were observed since 2000. For many states, this trend corresponded with rising YLL rates from interpersonal violence and chronic kidney disease. Nationally, age-standardised YLL rates for diarrhoeal diseases and protein-energy malnutrition markedly decreased, ranking Mexico well above comparator countries. However, amid Mexico's progress against communicable diseases, chronic kidney disease burden rapidly climbed, with age-standardised YLL and DALY rates increasing more than 130% by 2013. For women, DALY rates from breast cancer also increased since 1990, rising 12·1% (4·6–23·1%). In 2013, the leading five causes of DALYs were diabetes, ischaemic heart disease, chronic kidney disease, low back and neck pain, and depressive disorders; the latter three were not among the leading five causes in 1990, further underscoring Mexico's rapid epidemiological transition. Leading risk factors for disease burden in 1990, such as undernutrition, were replaced by high fasting plasma glucose and high body-mass index by 2013. Attributable burden due to dietary risks also increased, accounting for more than 10% of DALYs in 2013. Interpretation: Mexico achieved sizeable reductions in burden due to several causes, such as diarrhoeal diseases, and risks factors, such as undernutrition and poor sanitation, which were mainly associated with maternal and child health interventions. Yet rising adult mortality rates from chronic kidney disease, diabetes, cirrhosis, and, since 2000, interpersonal violence drove deteriorating health outcomes, particularly in men. Although state inequalities from communicable diseases narrowed over time, non-communicable diseases and injury burdens varied markedly at local levels. The dissonance with which Mexico and its 32 states are experiencing epidemiological transitions might strain health-system responsiveness and performance, which stresses the importance of timely, evidence-informed health policies and programmes linked to the health needs of each state. Funding: Bill & Melinda Gates Foundation, Instituto Nacional de Salud Pública.